Popular religion and ascetic practices : new studies on Mahimā Dharma - Banerjee-Dube, Ishita; Banerjee-Dube, Ishita (Studies in Orissan society, culture and history, 2008)
Papers presented at the International Seminar: Reconsidering Mahima Dharma : New Research Perspectives on Popular Asceticism in Orissa, held at Bhubaneswar on 23rd February 2002